Modelling Structured Domains Using Description Graphs and Logic Programming. - Magka, D; Motik, B; Horrocks, I (CEUR, 2012)
OWL 2 is widely used to describe complex objects such as chemical molecules; however, OWL 2 axioms cannot represent `structural' features of chemical entities such as having a ring. A combination of OWL 2, rules and description graphs (DGs) has been suggested as a possible solution, but an attempt to apply this formalism in a chemical Semantic Web application has revealed several drawbacks. Based on this experience, we present a radically different approach to modelling complex objects via a novel formalism that we call Description Graph Logic Programs. At the syntactic level, our approach combines DGs, rules, and OWL 2 RL axioms, but we give semantics to our formalism via a translation into logic programs interpreted under stable model semantics. The result is an expressive formalism that is well suited for modelling objects with complex structure, that captures the OWL 2 RL profile, and that thus fits naturally into the Semantic Web landscape. Additionally, we test the practical feasibility of our approach by means of a prototypical implementation which provides encouraging results.